FRI0634 STANDARD REFERENCE VALUES OF METACARPAL HEAD CARTILAGE THICKNESSMEASUREMENT BY ULTRASOUND IN HEALTHY SUBJECTS. (June 2019) - Cipolletta, Edoardo; Filippucci, Emilio; Matteo, Andrea DI; Hurnakova, Jana; Carlo, Marco DI; Pavelka, Karel; Grassi, Walter
Abstract : Background: The hyaline cartilage of metacarpal head (MH) is frequently involved in patients with chronic arthtritis. Moreover, in a recent study a high correlation has been found between the anatomical and sonographic (US) measurements of hyaline cartilage 1 . However, only very few data are available on the prevalence of pathological findings and the standard reference values in healthy subjects (H). Objectives: To determine the prevalence of the US abnormalities at metacarpal head (MH) in H, and to measure MH cartilage thickness (CT) in order to provide standard reference values. Methods: US examinations were performed on 944 metacarpophalangeal (MCP) joints of 118 consecutive H using a MyLab Twice (Esaote Biomedica, Genoa, Italy), equipped with a high frequency probe (up to 22 MHz). H were recruited among the staff of Rheumatology Department of the "Carlo Urbani" Hospital (Jesi, Ancona, Italy), students in medicine and patients' healthy relatives. Exclusion criteria were: hand pain (VAS score >1/10) or stiffness in the previous month or hard tissue enlargement of MCP, proximal and distal interphalangeal joints. The MH hyaline cartilage from II to V digits of both hands was scanned with the MCP joints in maximal flexion in longitudinal and transverse dorsal views, paying attention on maintaining an angle of 90° between the direction of the US beam and the cartilage surface 2 . CT was scored both semi-quantitatively (using a five-grade scoring system 3 ) and quantitatively (using the mean value of longitudinal and transverse measurements of the CT). Moreover, the presence of osteophytes and bone erosions was recorded. The association between CT and demographic data was analyzed. Results: Semiquantitative score: Cartilage damage was found in 21 out of 118 H (17.8%) and in 59 out of 944 MHs (6.3%): grade 1 and grade 2 in 43 (4.6%) and in 16 (1.7%), respectively. No grades 3 and 4 were detected. Osteophytes and bone erosions were respectively found in 12 (10.1%) and in 8 (6.7%) out of 118 H and in 24 (2.5%) and in 12 (1.3%) out of 944 MHs. A slight correlation between semi-quantitative score and the presence of osteophytes was found (r=0.16, p<0.01). No association between bone erosion and cartilage thinning was found. Quantitative assessment: A significantly thicker cartilage was found in males [0.71±0.10 mm (mean±SD)] than in females [0.68±0.12 mm, (mean±SD)] (p<0.01). No significant difference was found between left and right side for each digit (p>0.05). CT value of the II MH was significantly greater than the one of the other fingers (p<0.01). No difference was found between the CT values of III, IV and V MH (p>0.05). There was a significant association between the CT value and gender (r=0.39; p<0.01), age (r=-0.33; p<0.01), height (r=0.28; p=0.01) and grade of the semiquantitative scoring system (r=-0.19, p<0.01). No correlation was found between the CT value and weight (p=0.20). Conclusion: This study confirms the presence and provides data on the prevalence of US abnormalities at MH level in healthy individuals. Moreover, normal values for US CT of MH were reported. References: [1] Mandl P, Supp G, Baksa G, et al. Relationship between radiographic joint space narrowing, sonographic cartilage thickness and anatomy in rheumatoid arthritis and control joints. Ann Rheum Dis. 2015;74:2022-7. [2] Torp-Pedersen S, Bartels EM, Wilhjelm J, Bliddal H. Articular cartilage thickness measured with US is not as easy as it appears: a systematic review of measurement techniques and image interpretation. Ultraschall Med. 2011;32:54-61. [3] Filippucci E, da Luz KR, Di Geso L, et al. Interobserver reliability of ultrasonography in the assessment of cartilage damage in rheumatoid arthritis. Ann Rheum Dis. 2010;69:1845-8. Disclosure of Interests: None declared